Sample Survey of Chronic Obstructive Pulmonary Disease and Associated Risk Factors in Isfahan, Iran - Golshan, Mohammad (National Research Institute of Tuberculosis and Lung Disease, 2011)
BACKGROUND: The purpose of this cross-sectional study was to estimate the number of individuals with chronic bronchitis and/or chronic obstructive pulmonary disease in Isfahan. Our study results were compared with those of previous studies in Iran and similar studies in other countries. MATERIALS AND METHODS: As a part of a population-based, cross-sectional study, 2,200 randomly selected individuals aged 40 years or older were asked to take part in the survey; among whom, 1308 individuals (59.45%) agreed to fill out the respiratory questionnaire. This group consisted of 636 (48.6%) males and 672 (51.4%) females. Spirometric measurements were performed in 279 cases. COPD was defined by the “Global Initiative for Obstructive Lung Disease” criteria. RESULTS: One hundred-seven individuals (8.1%) fulfilled the clinical criteria for chronic bronchitis as the main sign of COPD. Multivariate analysis revealed that age and smoking were independent predictors for chronic obstructive pulmonary disease. CONCLUSION: It is concluded that the prevalence of chronic bronchitis symptoms is approximately the same in our population as compared with western countries. The frequency of clinical chronic bronchitis has risen in comparison to a previous study in Isfahan.